Interference of apoptosis in the pathophysiology of subarachnoid hemorrhage - Palade, C; Ciurea, Alexandru; Nica, D; Savu, R; Moisa, Horatiu (Asian Journal of Neurosurgery, 2013)
Programmed cell death is crucial for the correct development of the organism and the clearance of harmful cells like tumor cells or autoreactive immune cells. Apoptosis is initiated by the activation of cell death receptors and in most cases it is associated with the activation of the cysteine proteases, which lead to apoptotic cell death. Cells shrink, chromatin clumps and forms a large, sharply demarcated, crescent-shaped or round mass; the nucleus condenses, apoptotic bodies are formed and eventually dead cells are engulfed by a neighboring cell or cleared by phagocytosis. The authors have summarized the most important data concerning apoptosis in subarachnoid hemorrhage that have been issued in the medical literature in the last 20 years.
Keywords: Apoptosis; cell death receptors; programmed cell death; subarachnoid hemorrhage